Pengaruh Kompetensi Aparat Desa dan Penggunaan Aplikasi Sistem Keuangan Desa terhadap Kualitas Laporan Keuangan Desa - Katharina Yuneti; Valeria Eldyn Gula; Wihelmina Maryetha Yulia Jaeng (Universitas 45 Surabaya, 2024)
This research describes testing the influence of employee competency and use of village financial system applications on the quality of village financial reports. The research method used is quantitative with a survey approach. The data used in this research is a questionnaire. Data analysis using Multiple Linear Regression Analysis. The research results show that employee competency influences the quality of village financial reports, while the use of village financial system applications does not influence the quality of village financial reports and the internal control system has a positive influence on the quality of village financial reports. Based on the results of this research, the village government in Sikka Regency needs to improve various training and ensure that village officials understand the training material provided properly and correctly.